Analisis Kelayakan Kafe 1960 : Aspek Teknis, Keuangan dan Pasar di Palangka Raya - Dyah Septia Ningrum; Khusnul Khotimah; Astry Monica; Sopiatul Fitriah; Muhammad Farras Nasrida; Benius, Benius (FKIP, Universitas Palangka Raya, 2024)
This research evaluates the business feasibility of Café 1960 in Palangka Raya by analyzing its technical, financial, and market aspects. The study highlights strategic location, efficient operational management, and distinctive market characteristics as key contributors to the café's success. Financially, the café demonstrates strong feasibility, with a Payback Period of 7 months, a positive Net Present Value (NPV) of Rp107,550,555, and an Internal Rate of Return (IRR) of 42.91%. The café leverages unique menus and locally oriented marketing strategies to sustain market share amidst moderate competition. Using a qualitative descriptive approach, data were collected through interviews, field observations, and document analysis. The findings underline the importance of local market dynamics in smaller urban settings, offering insights into sustainable business practices for similar ventures in developing regions. This research contributes to the field by presenting a comprehensive feasibility analysis that integrates technical, financial, and market perspectives, focusing on the specific context of Palangka Raya's growing café industry.